Construction Of Kompakers Jogja's Identity Through Food Photography Challenge - Ariantini, Tiyas; Wibowo, Arif Ardy; Samsudin, Mat Redhuan (Universitas Telkom, 2024)
The gradual evolution of media alters the manner in which humans engage with one another. The media now serves as a tool for constructing one's identity. Instagram is one of the media platforms utilized. Instagram, a social media platform, is no longer solely utilized for personal purposes, but now serves as a community tool for disseminating information to its audience. One community that made use of this amenity is the Kompakers Jogja. This study examines the process by which members of the Kompakers Jogja develop their identities on the social media platform Instagram. The analysis is based on Gauntlett's theory of identity formation. The research methodology employed is qualitative, specifically utilizing the phenomenological approach to investigate the production of social reality. Through the utilization of observation and interview methodologies. This study utilizes seven informants as sources. The findings of this study indicate that individuals are actively shaping their identities on the social media platform Instagram by posting photos accompanied by captions. Three types of identity constructs are formed: professional and expertise identity, connection identity, and character identity.